Global Alterations in Mechanical Function in Healed Reperfused First Anterior Myocardial Infarction - Kramer, Christopher M.; McCreery, Charles J.; Semonik, Lori; Rogers, Walter J.; Power, Thomas P.; Shaffer, Amy; Reichek, Nathaniel (Journal of cardiovascular magnetic resonance, 2000)
Two-dimensional analysis techniques were applied to breathhold magnetic resonance (MR) tagged images in humans to better understand left ventricular (LV) mechanics 8 weeks after large reperfused first anterior myocardial infarction (Ml). Eighteen patients (aged 51 ± 13 yr, 15 men) were studied 8 ± 1 weeks after first anterior Ml as were 9 volunteers, (aged 30 ± 3, 7 men). Breathhold MR myocardial tagging was performed with short-axis images spanning the LVfrom apex to base. Myocardial deformation was analyzed from apical, mid-LV, and basal slices using two-dimensional analytic techniques and expressed as LI (greatest systolic lengthening), L2 (greatest systolic shortening), and β (angular deviation of LI from the radial direction). LV ejection fraction (EF) by MR imaging in the patients after MI was 45 ± 15%. The apex and midventricle in patients demonstrated reduced LI and L2 and increased P compared with normal subjects with the greatest abnormalities at the apex, as expected in anterior infarction. However, in addition, basal LI was lower than normal subjects (10 ± 6% versus 19 ± 7%, p < 0.0001) as was L2 (14 ± 7% versus 17 ± 6%, p < 0.04). P was greater than normal at the base (23 ± 20 degrees and 14 ± 10 degrees, p < 0.02). L2 correlated significantly with EF in the patient group (EF = 2.6 × L2 + 7, r = 0.68, p < 0.002). After healing of reperfused first anterior Ml, maximal lengthening and maximal shortening and the orientation of maximal strains are abnormal throughout the left ventricle, including mild abnormalities at the base. This suggests more diffuse abnormalities in regional mechanical function than simply within the zone of healed infarction.